(untitled) (Rajarshi Janak University Research Journal, 2025)
Background: Migrant workers significantly contribute to the development of destination countries, while countries of origin benefit from remittances and skills transfer. With the rising number of labour migrants, many face challenges such as health problems and work-related injuries. However, there is lack of studies exploring such problems faced by the labour migrants. This study aims to assess the health problems faced by Nepalese labour migrants in Malaysia and identify associated factors. Methodology A cross-sectional study was conducted among 325 Nepalese labour migrants who had worked in Malaysia and were selected conveniently. Data were collected using a semi-structured questionnaire through face-to-face interviews. Multivariate analysis was conducted on variables with p-values < 0.2 from bivariate analysis to identify significant predictors. Results Among 325 respondents, 47.7% reported experiencing health problems during their stay in Malaysia. Most (94.2%) had sought healthcare services, including government hospitals, private clinics, or company clinics. Factors such as number of roommates, overcrowded sleeping conditions, lack of cleanliness and hygiene, unclean toilets, lack of drinking water, and years lived in Malaysia were significantly associated with health problems.